IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH STRUCTURAL ANALYSIS - Juliana Sujadi; Fariska Wulandari (IKIP PGRI Pontianak, 2019)
This research was conducted to find out whether structural analysis can improve the students’ vocabulary and how significant the use of structural analysis improves the students’ vocabulary of class A first semester students of Business English and Management Concentration. This research was classroom action research which was done in two cycles. Field note and test were used as the instrument of data collecting. The data of the students’ pre-test and progress-test score were analyzed by using mean score and the data of observation was analyzed descriptively. The finding of this research was the students’ vocabulary was improved from the pre-test and the progress test of the first and second cycle. The mean score of the pre-test is 44.0. Then, the mean score of the first students’ progress test was 62.8, and 70.5 for the second progress test. And the result from the field note supported the finding of the test that was the students’ vocabulary improved from the first cycle to the second cycle after giving the treatment by the researcher.Key words: improving, vocabulary, structural analysis, classroom action research.